Contemporary venezuelan native cunning and its anchoring to history (El Taco en la Brea, 2020)
Native cunning is one of the most recognizably characteristic traits of Venezuelan ship. It sown people recognize it. It is a constant presence in the Venezuelan social bond, confirmed by its share dup keep among its dwellers. Cunning is a kind of socio-cultural fabric that is common among us. But precisely because of this, it shows its problematic nature in great extent. In most cases, cunning is interpreted as a wrong to ward the law and to others. It is openly recognized as a social problem about which, paradoxically, little has been systematized. The following paper proposes an argumentative path that shows the anchorages of this contemporary Venezuelan native cunning—understanding anchorage as a signifier that allows us to approach it as a symptom: the main thesis that will unfold by the end of this work.
Keywords: native cunning; symptom; social bond; Venezuela